Analisis Formulasi Enteral Bubuk Berbasis Tepung Tempe Dan Tepung Wortel Sebagai Inovasi Untuk Pasien Stroke - Nur'faizah, Hana; Reski, Sepsina; Widajati, Endang (Pontianak Nutrition Journal (PNJ), 2025)
Stroke is the leading cause of death and disability worldwide. One important nutritional intervention is the provision of enteral formulas, which can be made from local food ingredients such as tempeh and carrots. This study aims to evaluate the organoleptic aspects, nutritional content, and viscosity of enteral powder formulas based on tempeh flour and carrot flour. The method used is an experiment with three treatments: F1 (22:7), F2 (17:12), and F3 (19:10). The statistical analysis applied includes One Way ANOVA for energy, fat, and carbohydrate variables, as well as the Kruskal-Wallis test for protein variables and organoleptic tests. The results show significant differences in organoleptic tests (aroma: p=0.000; taste: p=0.000), viscosity (flowability: p=0.006), and nutritional content (energy: p=0.007; carbohydrates: p=0.029) with p < 0.05. However, there were no significant differences in organoleptic tests (color: p=0.847; texture: p=0.174) and protein (p=0.102) with p > 0.05. The formulation with the best organoleptic test is found in F2, while the formula with the highest energy density is found in F3